A Uniqueness Theorem for Linear Wave Equations (Journal of Partial Differential Equations, 2020)
The classical Huygens' principle asserts that the initial data of a wave equation determines the wave propagation in the domain of dependence of the support of the data. We provide a converse version of this theorem.
Keywords: Nehari manifold; quasilinear elliptic equation; Sobolev critical exponent